Personal and family factors for emotional distress in adolescents with chronic disease - Postigo-Zegarra, Silvia; Schoeps, Konstanze; Pérez-Marín, Marián; Lacomba-Trejo, Laura; Valero-Moreno, Selene (Frontiers in Psychology, 2024)
Introduction Physical and psychological comorbidity is a challenge for public health, especially in the adolescent stage due to the difficulties of this age. The salutogenic perspective emphasizes general psychological resources such as self-esteem but also highlights the role of contextual factors such as family members in promoting health. From this perspective, the objective of this study was to analyze the joint influence of demographic factors (sex, age and type of chronic disease), personal factors (self-esteem and perception of threat of the disease) and family factors (affection and communication, psychological and behavioral control) of risk of emotional distress (anxiety-depressive symptoms) in chronically ill adolescents. Methods The study is a cross-sectional design with 495 adolescents with chronic disease aged 12–16 years. In order to obtain the results, a linear methodology was used to compare means and perform regressions to predict belonging to the anxiety and depression typologies. Four typologies were constructed: typology I (high anxiety and depression scores); typology II (high anxiety and low depression scores); typology III (low anxiety and high depression scores) and typology IV (low anxiety and depression scores). Results The results were consistent with the salutugenic theory. Potential mediating or moderating roles of age, sex, self-esteem, perceived threat and psychological and behavioral control marked the differences between the typologies. Discussion This population could benefit from interventions focused on family flexibility.